Synthesis of TiO2 Nanofiber-Nanoparticle Composite Catalyst and Its Photocatalytic Decolorization Performance of Reactive Black 5 Dye from Aqueous Solution - Notodarmojo, Suprihanto; Sugiyana, Doni; Handajani, Marisa; Kardena, Edwan; Larasati, Amanda (Journal of Engineering and Technological Sciences, 2017)
In this study, synthesis of TiO2 nanofiber-nanoparticle composite photocatalyst was carried out and its photocatalytic decolorization performance was investigated. TiO2 nanofibers were developed by electrospinning. The TiO2 nanoparticle films were prepared by dipping the glass substrates into a sol solution made by sol-gel method. The TiO2 nanofiber-nanoparticle composite was immobilized on glass plates and annealed at 500 Â°C. The effects of pH and catalyst loading were studied during a photocatalytic decolorization experiment using simulated dyeing wastewater containing Reactive Black 5 (RB5). The photocatalytic decolorization performance with 60 min of UV-irradiation time using the TiO2 nanofiber-nanoparticle composite was found to be higher (94.4%) than that of the TiO2 nanofibers (75.5%) and the TiO2 nanoparticle catalyst (74.1%). An alkaline condition and high catalyst loading were found to be preferable to achieve optimum photocatalytic decolorization of Reactive Black 5 (RB5). The TiO2 nanofiber-nanoparticle composite could be recovered after reusing multiple times through re-annealing at a high temperature. TiO2 nanofibers based on a composite catalyst that is strongly immobilized on glass plates enlarges the prospect of the photocatalytic method as a compact, practical and effective advanced treatment process for effluents from textile wastewater.